(untitled) (Acta Polytechnica CTU Proceedings, 2016)
The aim of this paper is to elaborate a layout of the first operational concept of Rapid Services with 1 hour system travel time between Praha and Brno. Two basic methods are used – Integrated Periodic Timetable (periodic rendezvous of all services in IPT-nodes) and Operational Concept Economy Approach, as defined below by the author. In this paper, three recent high-speed railway concepts for the future so-called Rapid Services network of the Czech Republic are followed-up. The first one is an operational traffic planning study by Kalcík, Janoš et al. on behalf of Czech Ministry of Transport from 2010. The second one is the high-speed railway promoting book High Speed Rail Even in the Czech Republic by Šlegr et al. from 2012, with likely the most detailed concept of Rapid Services network. The third one is a paper on progress of the official spatial-technical studies for some future Czech high-speed lines by Šulc from 2014. The importance of achievement of 1 hour travel time between the largest agglomerations is briefly presented. The presented methodological approach, although soft and manager-oriented, comprises some firm principles: segmentation of high-speed train offer, so that more expensive rolling stock is not wasted by operation on long conventional line sections, consideration of system travel times for efficient rolling stock circuit, restriction of need for links from high-speed to conventional lines, and utilization of high-speed lines as a "rail highway". This approach is intended to be particularized iteratively, with every application. So, in this paper, first version of Operational Concept Economy Approach is introduced. The key idea is that passengers should be offered such travel times and service intervals (headways) and such number of direct services, which are adequate to their potential demand, but as much synergistic effect as possible should be strived to be achieved for every proposed construction (new or modernized one). Such approach goes towards economic efficiency, which is crucial indicator for political decision necessary for building, let alone EU co-funding of the construction. Experience shows that in many Czech feasibility studies, achievement of sufficient economic efficiency was the most complicated part of the study. Results show that an efficient operational concept can be designed not at the expense of runtimes between the largest cities.